Edukasi Perilaku Hidup Bersih Sehat (PHBS) Tingkat Rumah Tangga di Desa Geulanggang Baro - Dewi Maritalia; Agustina Agustina; Herrywati Tambunan (Universitas Baiturrahim, 2026)
Clean and Healthy Living Behavior (PHBS) is a series of behaviors practiced in everyday life with full awareness by individuals and families. PHBS needs to be implemented in every household by empowering each family member to know, want and be able to practice it in everyday life. The implementation of PHBS can prevent disease and improve the health of individuals, families, communities and the environment. This community service aims to increase public understanding, especially housewives about the indicators and importance of PHBS in everyday life. The method used is an educational approach through counseling on 10 PHBS indicators at the household level, including providing exclusive breastfeeding, weighing babies and toddlers, using clean water, washing hands with soap and running water, using healthy latrines, eradicating mosquito larvae, and not smoking in the house. The counseling activity was carried out in the multipurpose room of Geulanggang Baro Village on August 11, 2025, from 1:30 PM to 4:30 PM WIB, using infocus media, laptops and loudspeakers. Approximately 33 participants attended, consisting of housewives, young women, and men. Technically, the counseling session began with introductions between the community service team and the participants, followed by a presentation of the material and a question and answer session. Finally, an oral and written evaluation was conducted with the participants regarding the material presented. The results of the counseling session showed that almost all participants were able to name and answer questions posed by the community service team regarding PHBS at the household level. The conclusion obtained was that there had been an increase in participants' knowledge and understanding of PHBS at the household level.